An overview of some potential immunotherapeutic options against COVID-19 - Bayat, Maryam (Int Immunopharmacol, 2021)
After the advent of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) in the late 2019, the resulting severe and pernicious syndrome (COVID-19) immediately was deployed all around the world. To date, despite relentless efforts to control the disease by drug repurposing, there is no approved specific therapy for COVID-19. Given the role of innate and acquired immune components in the control and elimination of viral infections and inflammatory mutilations during SARS-CoV2 pathogenesis, immunotherapeutic strategies appear to be beneficent. Passive immunotherapies such as convalescent plasma, which has received much attention especially in severe cases, as well as suppressing inflammatory cytokines, interferon administration, inhibition of kinases and complement cascade, virus neutralization with key engineered products, cell-based therapies, immunomodulators and anti-inflammatory drugs are among the key immunotherapeutic approaches to deal with COVID-19, which is discussed in this review. Also, details of leading COVID-19 vaccine candidates as the most potent immunotherapy have been provided. However, despite salient improvements, there is still a lack of completely assured vaccines for universal application. Therefore, adopting proper immunotherapies according to the cytokine pattern and involved immune responses, alongside engineered biologics specially ACE2-Fc to curb SARS-CoV2 infection until achieving a tailored vaccine is probably the best strategy to better manage this pandemic. Therefore, gaining knowledge about the mechanism of action, potential targets, as well as the effectiveness of immune-based approaches to confront COVID-19 in the form of a well-ordered review study is highly momentous.